224k views
3 votes
X + 2y = 13
3x - 5y = 6

2 Answers

1 vote

Explanation:

Using Simultaneous Equation

Substitution method

Recall

x+2y=13. equ.1

3x-5y=6. equ.2

equ.1=

x-2y=13

x=13-2y. equ.3

Substitute 'x' into equ.2

3(13-2y)-5y=6

39-6y-5y=6

39-11y=6

collect like terms

39-6=11y

33/11=11y/11

therefore y=3

Substitute 'y' into equ.1, equ.2 or equ.3

Recall equ.3

x=13-2y

x=13-2(3)

x=13-6

therefore x=7

x=7, y=3

User Alex Terreaux
by
5.1k points
0 votes
What’s the question??
User Neolei
by
6.2k points